(untitled) (Journal of Kidney Cancer, 2023)
A third of patients with renal cell carcinoma (RCC) present with metastatic disease. Metastasis in RCC from small renal mass (SRM) (≤4 cm) is rare. We report a case of stage cT1a clear-cell RCC with low-risk features on pathology presenting with disproportionately large synchronous solitary metastasis to the transverse colon. He underwent resection of the mass with the involved transverse colon and adjoining mesocolon. Intestinal continuity was restored, following which partial nephrectomy was performed for the right renal tumor. Final pathology of the right renal mass confirmed clear-cell RCC. The large mass after immunohistochemistry profile confirmed metastasis from the renal tumor.